Quality of life in sarcopenia measured with the SarQoL®: impact of the use of different diagnosis definitions - Beaudart, Charlotte (Aging Clin Exp Res, 2017)
BACKGROUND: The SarQoL® is a recently developed quality of life questionnaire specific to sarcopenia. AIM: To compare the quality of life (QoL) of subjects identified as sarcopenic with that of non-sarcopenic subjects when using six different operational definitions of sarcopenia. METHODS: Participants of the SarcoPhAge study (Belgium) completed the SarQoL®. Among the six definitions used, two were based on low lean mass alone (Baumgartner, Delmonico), and four required both low muscle mass and decreased performance (Cruz-Jentoft, Studenski, Fielding, Morley). Physical assessments included measurements of muscle mass with dual energy X-ray absorptiometry, muscle strength with a handheld dynamometer and gait speed over a 4-m distance. RESULTS: A total of 387 subjects completed the SarQoL®. Prevalence of sarcopenia varied widely across the different definitions. Using the SarQoL®, a lower QoL was found for sarcopenic subjects compared to non-sarcopenic subjects when using the definitions of Cruz-Jentoft (56.3 ± 13.4 vs 68.0 ± 15.2, p < 0.001), Studenski (51.1 ± 14.5 vs 68.2 ± 14.6, p < 0.001), Fielding (53.8 ± 12.0 vs 68.3 ± 15.1, p < 0.001), and Morley (53.3 ± 12.5 vs 67.1 ± 15.3, p < 0.001). No QoL difference between sarcopenic and non-sarcopenic subjects was found when using the definitions of Baumgartner or Delmonico, which were only based on the notion of decreased muscle mass. DISCUSSION AND CONCLUSIONS: The SarQoL® was able to discriminate sarcopenic from non-sarcopenic subjects with regard to their QoL, regardless of the definition used for diagnosis as long as the definition includes an assessment of both muscle mass and muscle function. Poorer QoL, therefore, seems more related to muscle function than to muscle mass.